Isolation of Streptococcus bovis in a Patient with Undiagnosed Colon Cancer. A Case Report - Ledys Pérez Morales; Jorge Emilio Barletta del Castillo; Odette Quiñones Cherta (Medisur)
One of the bacterial agents commonly associated with colorectal cancer is Streptococcus bovis. Twenty five to 80 % of patients with Streptococcus bovis bacteremia develop colorectal tumors and the incidence of colonic neoplasia associated with S. bovis endocarditis has been shown to be 18 to 62 %. Hence, it was decided to present the case of a 57-year-old patient from an urban area with a 6-year history of diabetes mellitus type I and alcoholism, who was admitted to the hospital in Cienfuegos because of significant gastrointestinal bleeding and fever (39-40 o C). Streptococcus bovis was isolated from the blood culture. The patient died 72 hours after his admission. Autopsy results showed a moderately differentiated adenocarcinoma of the right colon.